SISTEM BEL DAN JADWAL PELAJARAN DI SEKOLAH BERBASIS IOT - Prasetya, Ariza; Hardiansyah, Hardiansyah; Surojo, Surojo; Silalahi, Parulian (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2025)
The integration of Internet of Things (IoT)-based systems in educational environments represents a strategic approach to improving time management efficiency. This study presents the design and implementation of an IoT-based automatic school bell and class scheduling system, controllable remotely via a mobile application. The system utilizes a NodeMCU ESP32 microcontroller as the main control unit, a DFPlayer Mini for automated audio playback, an LED Dot Matrix display for schedule visualization, and a speaker for audio output. The user interface is developed using the Blynk platform, and all programming is conducted through the Arduino IDE. Experimental results demonstrate that the system operates reliably, rings the bell in accordance with predefined schedules, and displays real-time schedule information. Furthermore, the integration of mobile control enhances user flexibility and operational convenience. This system contributes to the automation and optimization of scheduling tasks within educational institutions.